The Effectiveness of Finishing School Programmes from the Perspectives of Graduates and Employers (Malaysian Journal of Learning and Instruction, 2014)
Purpose â€“ This study examined the effectiveness of Finishing School programmes in enhancing the employability of graduates from institutions of higher learning. The perceptions of the graduates and employers towards the effectiveness of the programmes were analyzed. The effectiveness of Finishing School programmes evaluated through a graduate marketability outcome study and the expectations of employers with regard to the type of soft skills of graduates most needed by industries were also examined. Methodology â€“ Data for this study were obtained through a survey questionnaire administered to graduates and focus group interviews with selected employers. The primary data involved a large sample (n = 1092) of graduates from public universities and also 31 selected employers from various industries. The data were analysed using descriptive statistics, Chi-square tests, and a multinomial logit model. Due to the unavailability of a population frame, the data were collected using a convenient sampling design. Findings â€“ Graduates had a positive perception of the effectiveness of Finishing School programmes. However, in terms of the marketability outcome, Finishing school programmes currently